Comment on Education Returns of Wage Earners and Self-employed Workers - Henrik Jordahl; Panu Poutvaara; Juha Tuomala (Research Institute of Industrial Economics (IFN), 2008)
In a recent paper, García-Mainar and Montuenga-Gómez (2005) apply the generalized IV model of Hausman and Taylor to estimate education returns of wage earners and the self-employed in Portugal and in Spain. Our examination reveals several problems which relate to the validity and documentation of the instrumental variables, as well as the robustness of the results.
Keywords: C23; I21; J31; 330; Education; Entrepreneurship; Human capital; EGIV estimator; Humankapital; Bildungsertrag; Selbstständige; Angestellte; Schätzung; Finnland